2022
DOI: 10.1002/jsfa.12191
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sonicated gluten protein and subsequent rheological properties of model dough and noodles

Abstract: Background The present study aimed to investigate the effects of the thermo‐mechanical and rheological properties of a wheat gluten‐sonicated model dough and noodles, as well as the effects of ultrasonic frequency (20, 28, 40, 68 and 80 kHz) on the functional properties and structural features of gluten. Results Water absorption, stability and developmental time, and viscoelastic behavior of gluten‐sonicated model dough were all found to be improved. Water absorption, tensile resistance and stretching distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…This could be explained to the fact that the internal stress of dough sheets was relieved, and the further hydration of gluten protein under higher humidity helped to enhance the springiness of gluten network (Yadav et al ., 2006). Studies have shown that the increase in breaking distance meant that the noodles were more ductile and less likely to break (Guo et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained to the fact that the internal stress of dough sheets was relieved, and the further hydration of gluten protein under higher humidity helped to enhance the springiness of gluten network (Yadav et al ., 2006). Studies have shown that the increase in breaking distance meant that the noodles were more ductile and less likely to break (Guo et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%